2014
DOI: 10.1039/c4ra05034g
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of boronic acid-functionalized nanoparticles via boronic acid–diol complexation for drug delivery

Abstract: We presented here a facile strategy for fabricating boronic acid-functionalized nanoparticles based on the complexation of phenylboronic acids in poly(3-methacrylamido phenylboronic acid) (PMAPBA) and glucose moieties in dextran via boronic acid-diol interactions. The formation of boronate crosslinked nanoparticles was confirmed by Fourier transform infrared spectrometry, thermal analysis, transmission electron micrographs, dynamic light scattering and UV spectrometry. The nanoparticles were well dispersed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…Then, the largest weight loss occurred from 280 to 350 °C. These results are in accordance with a previous report showing the thermal degradation of dextran . In the case of nanofibers containing PO and DCPD nanodroplets, three stages were observed in the decomposition of the materials.…”
Section: Resultssupporting
confidence: 93%
“…Then, the largest weight loss occurred from 280 to 350 °C. These results are in accordance with a previous report showing the thermal degradation of dextran . In the case of nanofibers containing PO and DCPD nanodroplets, three stages were observed in the decomposition of the materials.…”
Section: Resultssupporting
confidence: 93%
“…The swelling mechanism is caused by the shift in the equilibrium of different boronic acid species toward the anionic tetrahedral form upon binding to diols such as those on sugars, which causes osmotic swelling of the hydrogels . Alternatively, boronic acid‐based polymers can form a hydrogel upon complexation with diol‐containing polymers in the presence of insulin, and later be competitively displaced by glucose to dissolve the hydrogel and release insulin …”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. reported nanoparticles for drug release formed by poly(3‐methacrylamido PBA) and dextran . The complexation‐induced self‐assembly of two polymers formed nanoparticles in which insulin could be loaded and released in response to the addition of glucose.…”
Section: Stimuli‐responsive Release Systemsmentioning
confidence: 99%
“…Zhao et al reported acid-responsive micelles as drug delivery vehicles constructed using dextran-b-poly(L-lysine) modified with PBA moieties. [50] The block copolymer formed shell-cross-linked micelles via boronate-dextran interactions. Doxorubicin loaded in the hydrophobic core was released after endocytosis.…”
Section: Nanomaterials For Ddsmentioning
confidence: 99%